Development Of WO3 Catalytic Film For Detection Of Ethanol - Lim, Guat Wei (2011)
Tungsten oxide (WO3) films deposited on alumina substrate were prepared by chemical vapor deposition (CVD) using tungsten hexacarbonyl (W(CO)6) powder as precursor. The structural characterization was performed using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and atomic force microscope (AFM). The responses of WO3 films towards 500 ppm of ethanol vapor were investigated at operating temperatures of 150 to 550oC. Optimization on the preparation condition parameters was performed using one-factor-at-a-time technique. The results showed that sensitivity of the developed WO3 film varied according to its preparation condition which included deposition temperature (200 to 350oC), annealing temperature (500 to 700oC) and ratio Ar(W(CO)6)/O2 (1/6 to 1/3).